Laser wobble welding of steel to Aluminium busbar joints for Li-ion battery packs. (July 2022) - Chelladurai Asirvatham, M; Collins, Sam; Masters, Iain
Highlights: Laser wobble welding of thin Steel tabs to thick Aluminium busbar for Lithium-ion battery packs. Weld geometry, microstructure, mechanical strength, and electrical contact resistance investigated. Development of optimum laser-wobble parameters to achieve high mechanical and electrical properties. A new joining solution for cost-effective aluminium busbars in Electric Vehicle manufacturing. Abstract: In this work, Laser wobble welding of Steel to Aluminium busbar joints was investigated for Li-ion battery pack applications. The effect of wobble amplitude on the properties of the weld was studied. It is observed that wobble amplitude significantly influenced the weld geometry, microstructure, mechanical strength, and electrical resistance. As wobble amplitude increases the weld depth reduces linearly and the severity of weld cracking was significantly reduced. Welds with an aspect ratio below 1, produce almost a crack-free microstructure. The optimum wobble amplitude was found to be 0.8–1 mm for the selected laser power density. Under optimum parametric conditions, the weld strength reaches 1 KN, equalling that of the thin steel sheet. In addition, the optimum welds showed a low volume of intermetallic phase formation which improved both electrical conductivity and tensile strength. The results of this study facilitate an effective joining solution for a cost-effective aluminium busbar material to steel-cased cylindrical cells.